Auditoría de Gestión para medir la eficiencia y eficacia de la empresa Incoreg Cía Ltda. ubicada en la ciudad de Riobamba, durante el período 2021. - Parra Guzmán, Bryan David (2023)
The investigation project was developed to elaborate a management Audit to measure the efficiency and effectiveness of the company Incoreg Cía. Ltda. Located in the city of Riobamba during the period 2021, all this work began with the due problem statement and the theoretical framework consisting of dependent and independent variables, generalities of the company, and its review. In the same way is mentioned the research methodology, where reference is made to the deductive method since they determined the concepts, principles, rules, and regulations that regulate the management audit; the analytical method was also used because it contributed to the evaluation to specific components where more attention is needed due to a large number of existing problems in the company. Subsequently, the management audit phases were applied, the same ones that are the planning, execution, and communication of results; all this was done with the collection of information competent and sufficient to prepare the work papers, and the findings were established.